2021
DOI: 10.1242/dev.190793
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the mammalian maternal-to-embryonic transition by eukaryotic translation initiation factor 4E

Abstract: Eukaryotic translation initiation factor 4E (eIF4E) mediates CAP-dependent translation. Genetic and inhibitor studies show its expression was required for the successful transition from maternal to embryonic control of mouse embryo development. eIF4E was in the oocyte and in the cytoplasm soon after fertilization, and at each stage of early development. Functional knockout (Eif4e−/-) by PiggyBac (PB) [Act-RFP] transposition caused peri-implantation embryonic lethality due to the failure of normal epiblast form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…[ 23 ] It has been reported that eIF4E is distributed evenly and also present in the vicinity of chromosomes after GVBD during oocyte maturation. [ 50 ] Through a comparison of the eIF4E1B targets with eIF4E targets, it was found a group of genes overlapped with the genes targeted to eIF4E1B. GO analysis revealed the overlapped function between eIF4E1B and eIF4E targeted genes including the process of the meiotic cell cycle (Figure 5F).…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] It has been reported that eIF4E is distributed evenly and also present in the vicinity of chromosomes after GVBD during oocyte maturation. [ 50 ] Through a comparison of the eIF4E1B targets with eIF4E targets, it was found a group of genes overlapped with the genes targeted to eIF4E1B. GO analysis revealed the overlapped function between eIF4E1B and eIF4E targeted genes including the process of the meiotic cell cycle (Figure 5F).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in other MEGs have also been associated with human preimplantation embryo arrest, including CDC20 (cell division cycle 20), which helps the transition from metaphase to anaphase [63]; TRIP13 (thyroid hormone receptor interactor 13), which is a component of the spindle assembly checkpoint [64,65 ▪▪ ]; BTG4 (B-cell translocation gene 4), which mediates degradation of maternal mRNAs upon maternal-to-zygotic transition [66]. Studies in model systems support these findings and identify additional MEGs associated with embryonic developmental arrest [58,67–75] (Table 1).…”
Section: Embryonic Arrestmentioning
confidence: 93%
“…A number of studies associated TUBB8 mutations with oocyte maturation defects ]; BTG4 (B-cell translocation gene 4), which mediates degradation of maternal mRNAs upon maternal-to-zygotic transition [66]. Studies in model systems support these findings and identify additional MEGs associated with embryonic developmental arrest [58,[67][68][69][70][71][72][73][74][75] (Table 1).…”
Section: Mutations In Maternal Effect Genesmentioning
confidence: 93%
“…encoding ANK2 [ 55 ]). Post-fertilization, mTOR directed phosphorylation of EIF4EBP1 is reported as an important translational regulator of the maternal-to-embryonic transition [ 56 ]. In early mouse blastocysts (but not earlier cleavage stages), partial pharmacological mTORi (targeting mTORC1 and mTORC2) results in prolonged but reversible and viable ex vivo paused development, akin to natural hormonally induced in vivo diapause [ 57 ].…”
Section: Introductionmentioning
confidence: 99%